ECONOMIC CHANGE AND TRANSITION OF MALAY SOCIETY IN MALAYA IN LATE NINETEENTH AND EARLY TWENTIETH CENTURIES - Abdullah, A Rahman Tang (SEJARAH: Journal of the Department of History, 2017)
This article discusses economic change and its relevance to the consciousness and transition in Malay society during British colonial rule in Malaya. The period of this study is the late nineteenth and early twentieth centuries. In this context, the fundamental concept of economic change is applied to the change f-oin self-sufficiency or subsistence to commercialism. The word 'consciousness' here is refer to the extent to which Malay society in general began to realize and was prepared to adapt to the new phenomena of economic changes. The word 'transition' here refers to the slow pace in the process of economic change in their involvement, practice and types of economic activities which manifested a distinction between traditional and modern orientations. The subject of discussion is composed of the aspects of traditional economy in the nineteenth century and general features in the process of transition in the Malay society such as land, labour utilization, padi cultivation, agricultural credit facilities and commercialism.